How to recognize an HIV-infected patient in dental practice - Latković Marina (Serbian Medical Society - Dental Section, Belgrade, 2007)
The human immunodeficiency virus (HIV) belongs to the family of retroviruses, the subfamily of lentiviruses and can be found in all body fluids. Virus concentration in body fluids determines the way of HIV transmission (through sexual contact, blood and blood products, vertical transmission). The results from literature indicate that, among the first manifestations of HIV, there are gingival and periodontal changes. Besides, certain number of opportunistic infections start and manifest themselves in the oral cavity. The aim of this paper was to present the most frequent changes in the oral cavity, such as: HIV gingivitis, HIV periodontitis, Candidiasis (pseudomembranous, erythematous, hyperplastic and agular cheilitis), hairy leukoplakia, HSV1 and Kaposi sarcoma. .